Picture supported communication in Africa: Fundamentals, examples and recommendations for appropriate communication and processes in rural development programmes in sub-Saharan Africa - Hoffmann, Volker (CTA / Margraf Verlag, 2002)
The potential of pictorial communication is examined from a theoretical perspective. This is followed by a discussion of communication with illiterate people, and case-studies of instances where pictorial communication has been developed and used successfully in Africa.